University Education for Business : a Study of Existing Needs and Practices - Bossard, James H. S. (University of Pennsylvania Press, 2017)
An exhaustive survey of the subject, from both the economic and academic points of view, with pertinent suggestions for a closer harmony between collegiate training and the modern business world.
Keywords: Business education -- United States.; Universities and colleges -- United States.; Enseignement commercial -- États-Unis.; Universités -- États-Unis.; BUSINESS & ECONOMICS -- Education.; Business education; Universities and colleges; United States